The role of gamification in sustainable teacher education: Examining concept images of curriculum elements using a solomon four-group design - Funda Uysal (PLoS ONE, 2026)
Despite the critical importance of curriculum literacy for effective teaching, developing pre-service teachers’ understanding of abstract curriculum elements remains a persistent and inadequately addressed challenge in teacher education worldwide. This research aimed to investigate the effects of gamification-supported teaching on pre-service teachers’ concept images (mental representations) of curriculum elements. The study employed a Solomon four-group experimental design (a robust design controlling for pretest effects) with 122 pre-service teachers studying at the Faculty of Education of a state university. Gamification activities based on individual and group work were implemented in the experimental groups (n = 61), while traditional teaching was used in the control groups (n = 61). Data were collected through a concept image questionnaire consisting of open-ended questions regarding curriculum elements (objectives, content, learning experiences, and evaluation) and student journals for reflective learning experiences from experimental group participants. The findings revealed that gamification-supported teaching had a substantive effect on concept images of curriculum elements, with large effect sizes for content (d = 1.59) and total score (d = 2.04). No significant pretest effects were observed, confirming methodological adequacy. Qualitative analysis revealed increased motivation (52 coded segments), enhanced conceptual understanding (47 segments), and interest-curiosity (43 segments) as primary themes. These findings demonstrate that gamification-supported flexible learning positively impacts both cognitive and affective outcomes. These results, consistent with similar studies in international literature, suggest that the gamification approach can be effective across different educational systems. These findings also have potential to contribute to the improvement of teacher education in achieving the “Quality Education” goal (SDG 4) within the United Nations’ Sustainable Development Goals framework. In conclusion, gamification-supported teaching can be utilized in teacher education as an effective approach for teaching abstract concepts such as curriculum elements. This research contributes to the teacher education literature by combining concept image theory with the gamification approach. Additionally, when evaluated from a sustainable teacher education perspective, the potential of the gamification approach as a pedagogical tool to support pre-service teachers’ long-term professional development has been demonstrated.